The U.S. and Allies’ Forward-Based BMD Systems: An Emerging Threat to Strategic Stability - I. Kuznetsov (Международная аналитика, 2017)
The subject of this expert study is an evaluation of risks and potential threats of globalization of the U.S. and the allied BMD systems as well as of their sea-based deployments as the most important component of integrated forward-based BMD systems. Negative consequences of the large-scale deployments of these systems for negotiating strategic arms limitations as well as for reversibility of the existing treaties are evident in the midterm perspective.The versions of “moderate” qualitative and quantitative estimations of these plans and programs promoted by the U.S. and allied countries allow to become firmly convinced about intentions to create the phenomena of “a window of vulnerability” for the Russia’s SLBM and ICBM retaliation potential. This temporal interval tends to widen, owing to a lower limit by a deployment closer to seashore of defense installations and objects in the depth of territory, as well as, by a shorter time-reaction to launches of the strategic retaliation forces by sea-based BMD’s.The most possible scenarios of the deployment of ships equipped with BMD’s and organized in groups that are engaged in “active-offensive” missions show the unavoidable necessity to include “a less favorable scenario” in the Russia’s strategic planning. The calculations adduced by the author give serious grounds to suggest that realization of corresponding plans of shipbuilding and deployments in the mid-term perspective will create conditions for reversibility of the existing strategic balance and totally undermine negotiating processes on arms control.